Lived religion and lived development in contemporary society - Madigele, Tshenolo Jennifer (Journal for the study of religion, 2025)
This book review critically examines Lived religion and lived development in contemporary society. The book honors Wilhelm Gräb. It explores the complex link between lived religion and development using interdisciplinary, empirical, and decolonial frameworks. The book offers insights into practical theology, indigenous epistemologies and ecological ethics. Its strengths include an African focus and theoretical innovations. Limitations exist in conceptual density and chapter quality. The book's importance for Southern Africa will be discussed. Recommendations for future scholarly inquiry will conclude this review.